ASPP and iASPP: Implication in cancer development and progression - Li, Y; Ahmad, A; Sarkar, F H (Cellular and Molecular Biology, 2015)
The well-known guardian of genome, p53 plays critical roles in the induction of apoptosis typically upon DNA damage whereas mutant p53 containing cells are unable to undergo apoptosis which leads to aggressive tumor growth and drug resistance. Moreover, another molecule regulating wild-type p53 function is ASPP (apoptosis stimulating proteins of p53) family. ASPP family consists of ASPP1 and ASPP2, and functions as tumor suppressors whereas the inhibitor of ASPP (iASPP) functions as oncogene. By binding to apoptosis regulating proteins such as p53, p63, p73, Bcl-2, NF-ÎºB p65, etc., ASPP1 and ASPP2 promote apoptosis while overexpression of iASPP inhibits apoptotic cell death typically after DNA damage. In cancer cells, the aberrant expressions of ASPP1, ASPP2 and iASPP have been observed, especially, the high expression of iASPP in cancers is associated with worse disease status, therapy resistance and poor survival of patients with cancers. The molecular interactions between the members of ASPP family and their binding proteins in apoptotic pathway together with other regulators such as miR-124, NF-ÎºB regulated Twist, snail, etc. form a complex signal transduction network to control apoptosis and tumor growth. Therefore, targeting ASPP family could regulate the aberrant communications in the signal transduction network to induce apoptosis and drug sensitivity. Several peptides, miRNAs and natural agents have been used to target ASPP family and show encouraging results in the induction of apoptosis of cancer cells; however, more in vivo animal studies and clinical trials are needed to confirm the true value of targeting ASPP family in the treatment of cancers.